The Presidential Regime in the 1993 Constitution - Bernales Ballesteros, Enrique (2016)
In this article, the author makes a critical analysis of the political regime in the 1993 Constitution. He begins analyzing the institution of the Presidency of the Republic, along with its vices and defects, criticizing the concentration of power in the figure of the President and the authoritarian management of his attributions, characteristics that are meaningless in a republic system. Thus, he concludes with a new vision of the figure of the President of the Republic and his attributions in order to achieve an improvement in the functioning and efficiency of the State, without affecting the democratic balance.